Injectable Poly‐l‐Lactic Acid for Human Immunodeficiency Virus–Associated Facial Lipoatrophy: Cumulative Year 2 Interim Analysis of an Open‐Label Study (FACES) - Bassichis, Benjamin; Blick, Gary; Conant, Marcus; Condoluci, David; Echavez, Michael; Eviatar, Joseph; Gold, Michael H.; Hamilton, Tiffani; Hanke, C. William; Humble, Gail; LaMarca, Anthony; Daro‐Kaftan, Elizabeth; et al. (Dermatologic surgery, 2012)
Background Studies of injectable poly‐l‐lactic acid (PLLA) in human immunodeficiency virus (HIV)‐associated facial lipoatrophy have predominantly included male Caucasians. Objective To report cumulative year 2 interim study results examining the safety and efficacy of injectable PLLA in subjects with HIV categorized according to Fitzpatrick skin type and sex. Materials and Methods This is an ongoing open‐label, multicenter, 5‐year study of 290 treated subjects. After correction with injectable PLLA, subjects are being followed annually. Primary end points include incidence and severity of treatment‐emergent adverse events (TEAEs). Secondary end points include mean change from baseline of James scale severity grade and treatment satisfaction. Results At 2 years, TEAE incidences were: potentially related to study product (n = 53,18.3%) or injection procedure (n = 71, 24.5%), injection‐site nodules (n = 24, 8.3%) and papules (n = 25, 8.6%). No hypertrophic scars, keloids, or product‐related serious TEAEs were reported. Mean improvement in James scale grade for all groups was 1.4 (p < .001), and 89.4% of subjects and 95.5% of physicians rated treatment satisfaction as very good or excellent. Conclusion At 2 years, injectable PLLA is a safe and effective long‐term treatment for HIV‐associated facial lipoatrophy regardless of Fitzpatrick skin type; confirmation of these results will be needed at the completion of this 5‐year study.